A spatial inventory of glacial, periglacial and rapid mass movement forms on part of Marion Island : implications for Quaternary environmental change - Meiklejohn, K.I. (Ian) (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2001.